ANALISIS PERAN BIOINFORMATIKA DALAM PENGOLAHAN DAN INTERPRETASI DATA GENOMIK - Inayati Rahmi; Dwi Marlen Untary; Utami Ariyasra; M. Syahputra; Herman Susilo (Smart Education, 2026)
Abstract: The rapid development of genome sequencing technologies has generated large volumes of biological data that require complex and structured analytical methods. In this context, bioinformatics plays a crucial role as a multidisciplinary approach that integrates biology, computer science, and statistics to efficiently process and interpret genomic data. This study aims to analyze the role of bioinformatics in the processing and interpretation of genomic data and its contribution to the advancement of molecular biology research. The method used in this study is a literature review by examining various scientific sources related to bioinformatics and genomic data analysis. The results show that bioinformatics plays a role in various stages of genomic analysis, including sequencing data processing, alignment, gene annotation, and genetic variation analysis. In addition, the use of bioinformatics algorithms and software enables researchers to identify genetic patterns and relationships among genes more accurately and efficiently. According to Andreas D. Baxevanis, bioinformatics is a key component in managing large-scale biological data, especially in the modern genomics era. This is also supported by David W. Mount, who states that computational analysis is essential for understanding genome structure and function. Thus, bioinformatics has a strategic role in supporting the processing and interpretation of genomic data and serves as a fundamental basis for the development of biotechnology research and precision medicine. This study is expected to provide a more comprehensive understanding of the importance of bioinformatics in genomic data analysis. Keywords: Bioinformatics, Genomics, Data Analysis, DNA Sequencing, Molecular Biology Abstrak: Perkembangan teknologi sekuensing genom telah menghasilkan data biologis dalam jumlah besar yang memerlukan metode analisis yang kompleks dan terstruktur. Dalam konteks ini, bioinformatika berperan penting sebagai pendekatan multidisiplin yang menggabungkan ilmu biologi, komputer, dan statistika untuk mengolah serta menginterpretasikan data genomik secara efisien. Penelitian ini bertujuan untuk menganalisis peran bioinformatika dalam pengolahan dan interpretasi data genomik serta kontribusinya terhadap perkembangan penelitian biologi molekuler. Metode yang digunakan dalam penelitian ini adalah studi literatur dengan mengkaji berbagai sumber ilmiah terkait bioinformatika dan analisis genomik. Hasil kajian menunjukkan bahwa bioinformatika berperan dalam berbagai tahapan analisis genomik, seperti pemrosesan data sekuensing, penyelarasan (alignment), anotasi gen, serta analisis variasi genetik. Selain itu, penggunaan algoritma dan perangkat lunak bioinformatika memungkinkan peneliti untuk mengidentifikasi pola genetik dan hubungan antar gen secara lebih akurat dan efisien. Menurut Andreas D. Baxevanis, bioinformatika merupakan komponen kunci dalam pengelolaan data biologis skala besar, terutama dalam era genomik modern. Hal ini juga didukung oleh David W. Mount yang menyatakan bahwa analisis komputasional sangat penting dalam memahami struktur dan fungsi genom. Dengan demikian, bioinformatika memiliki peran strategis dalam mendukung pengolahan dan interpretasi data genomik, serta menjadi fondasi utama dalam pengembangan riset bioteknologi dan kedokteran presisi. Penelitian ini diharapkan dapat memberikan pemahaman yang lebih komprehensif mengenai pentingnya bioinformatika dalam analisis data genomik. Kata kunci: Bioinformatika, Genomik, Analisis Data, Sekuensing DNA, Biologi Molekuler